UNCOVERING THE CONSUMER BEHAVIOR AMONG GENERATION Z: A BIBLIOMETRIC ANALYSIS - Prima Ratna Sari; Fuad Abdul Fattah; Dea Izza Pantari; Novia Tri Hapsari (Jurnal Manajemen Pemasaran, 2025)
This study aims to understand the consumer behavior of Generation Z using a bibliometric approach. The analysis technique uses VOSviewer with 235 articles collected from the Scopus database as the research object. Then, filtering was carried out based on the field of study, document type, year of publication, keywords, English language, and relevance to the topic, resulting in 32 articles from several stages of filtering. The findings of this study indicate that consumer behavior among Generation Z tends to be oriented toward or characterized by green consumerism and sustainable consumption. This pioneering study can serve as a foundation for further research exploring environmental concerns and green purchase intention in consumer behavior among Generation Z, contributing significantly to the literature on consumer behavior and generational groups.